2008
DOI: 10.1016/j.domaniend.2007.05.002
|View full text |Cite
|
Sign up to set email alerts
|

Central insulin suppresses feeding behavior via melanocortins in chicks

Abstract: Growing evidence suggests that insulin interacts with both orexigenic and anorexigenic peptides in the brain for the control of feeding behavior in mammals. However, the action of central insulin in chicks has not yet been identified. In the present study, we investigated the effects of central injection of insulin on feeding behavior in chicks. Intracerebroventricular (ICV) administration of insulin, at doses that do not influence peripheral glucose levels, significantly inhibited food intake in chicks. Centr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
42
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(43 citation statements)
references
References 35 publications
1
42
0
Order By: Relevance
“…Tokushima et al (2003) reported that plasma insulin levels in chicks of 1 to 7 days of age were lower than those in chicks of 10 to 28 days of age. Central administration of insulin significantly decreased NPY mRNA levels in chick brain stem (Shiraishi et al, 2008). In addition, insulin receptors are co-localized with NPY-containing neurons in the hypothalamus infundibular nucleus (Shiraishi et al, 2011).…”
Section: Resultsmentioning
confidence: 88%
“…Tokushima et al (2003) reported that plasma insulin levels in chicks of 1 to 7 days of age were lower than those in chicks of 10 to 28 days of age. Central administration of insulin significantly decreased NPY mRNA levels in chick brain stem (Shiraishi et al, 2008). In addition, insulin receptors are co-localized with NPY-containing neurons in the hypothalamus infundibular nucleus (Shiraishi et al, 2011).…”
Section: Resultsmentioning
confidence: 88%
“…The brain integrates information from peripheral hormones, such as leptin, insulin and gut hormones, and consequently regulates food intake: adiposity hormones such as leptin and insulin are secreted in proportion to body fat and suppress food intake, whereas gut hormones are secreted before or after meals and regulate food intake (Woods, 2009;Sam et al, 2012;Williams and Elmquist, 2012). In chickens, central administration of leptin (Denbow et al, 2000) and insulin Shiraishi et al, 2008) suppresses food intake. However, there is much debate on the physiological significance of leptin and insulin as adiposity hormones in birds.…”
Section: Introductionmentioning
confidence: 99%
“…Co-localisation of INSR and a-MSH proteins was also observed in the arcuate nucleus (Shiraishi et al, 2011). Two independent studies in chicks reported increased gene expression of POMC in the chick brain after central INS injection but no effect on AGRP mRNA in contrast to an inhibitory effect on NPY mRNA (Honda et al, 2007;Shiraishi et al, 2008). The apparent absence of an inhibitory effect of INS on AGRP gene expression may point to a regulatory difference between birds and mammals although observations need to be extended to adult chickens and to other species.…”
Section: Regulation Of Agrp and Pomc Gene Expression By Other Neuroenmentioning
confidence: 80%
“…It stimulates POMC gene expression and inhibits that of NPY and AGRP, corresponding to an inhibitory effect of centrally-administered INS on food intake (Porte et al, 2002). INS also inhibited food intake after central injections in domestic chicks, an effect blocked by melanocortin receptor antagonists (Honda et al, 2007;Shiraishi et al, 2008). Chick NPY neurons were demonstrated to co-express insulin receptor (INSR) mRNA and it is likely, but was not determined, that those same individual neurons expressed AGRP given the co-expression of NPY and AGRP mRNAs previously observed in birds (Boswell et al, 2002;Shiraishi et al, 2011).…”
Section: Regulation Of Agrp and Pomc Gene Expression By Other Neuroenmentioning
confidence: 95%